Understanding employees’ deviant behaviour: the role of agreeableness and stress related to work - Hadi Farhadi,; Rohany Nasir,; Fatimah Omar,; Nouri, Abolghasem (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
These days the majority of organizations struggle to overcome employees’ misbehavior. Understanding why a phenomenon occurs, Employers and industrial organizational psychologists are interested to find factors contributing to such behaviors. The objectives of this study were to investigate the relationship between job stress and agreeableness (a type of personality traits) with employee deviant behaviors. Data were collected through 212 employee of an organization in Malaysia. The results showed that both job stress and agreeableness predict workplace deviant behavior. Results found that there is a positive relationship between job stress and workplace deviance and negative relationship between agreeableness and deviant behavior. It was also shown that agreeableness moderate the relationship between job stress and workplace deviant behavior. Implications for future research are discussed.